Energy and entropy flux of the quantum Markovian process through an interacting demon-bit system with squeezed thermal reservoirs - Yang, Guangzhao (Nanyang Technological University, 2024)
One of the purposes of the information ratchet, which contains a demon system and bits system, is to mediate the thermodynamics, including energy and entropy flux, between a hot and a cold reservoir. Wherein the demon-bits system is generalized into the quantum regime, therefore demonstrating interesting quantum thermodynamical properties by using the phenomelogical GKSL master equation for the Markovian process.